18 THE IMPACT OF TRAINING MEDICAL ASSISTANTS TO PROVIDE SMOKING CESSATION COUNSELING TO AN UNDERSERVED PATIENT POPULATION. (1st January 2005) - Moore, E.; Keerbs, A.
Abstract : Background: Health care providers have experimented with ways to implement smoking cessation education and assistance into the clinic visit. The inclusion of smoking status as the fifth vital sign has been one way. At most clinics, the medical assistant has the first contact with the patient and documents the patient's smoking status along with other vital signs. This brief contact provides an opportunity to initiate dialogue about smoking cessation. Our study seeks to measure the effectiveness of the medical assistant as a smoking cessation educator. We anticipate patients will report an increased awareness of smoking cessation programs and a higher interest in pursuing a smoking cessation program. Study Design: and Methods: The study was conducted at the Bothell-Kenmore Community Health Clinic in King County, Washington in two 3-week blocks. In the first phase, medical assistants gave all smokers a 12-item survey regarding smoking cessation. At the conclusion of the control period, the medical assistants took part in a one-hour class on providing education and smoking cessation assistance. Following the class, the medical assistants continued administering the same surveys to current smokers and were encouraged to educate patients on smoking risks and cessation. Results: 43 surveys were collected in the control period and 42 in the experimental period. Experimental group subjects were more likely to positively respond to questions regarding the helpfulness of the clinic visit and in the level of interest in starting a smoking cessation program. While experimental group subjects were more likely to report that they were advised to quit smoking, that they discussed cessation with the doctor and that they were given education materials, this difference did not reach statistical significance. Conclusion: Bringing the medical assistant into the smoking cessation process appears to increase patient's self-reported motivation to quit. Benefits in other areas, such as improved patient education penetrance, would likely be seen in a larger sample size.